Management reforms in the Polish and Hungarian local government - Rajca, Lucyna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa, UAM, 2020)
The study aims to compare management reforms in the Hungarian and Polish local government structures which were introduced at the beginning of the transformation of the socio-political system and during the first two decades of the 21st century. The analyses show that local governments in both countries have implemented solutions derived from different management paradigms, which are in many respects contradictory. In the process of implementing management reforms in the local governments of the two countries there have been both convergent and divergent trends. The public administration reforms in Hungary after 2010 reflect a coherent vision of a strong and centralized state and are intended to ensure effective resolution of social problems. The market and civil society have been given a subordinate role. As far as the Polish local government model is concerned, currently it is difficult to indicate one organizational model constituting a coherent whole.

Celem opracowania jest porównanie reform zarządzania w węgierskim i polskim samorządzie terytorialnym wprowadzanych od początku transformacji ustrojowej i w okresie dwóch pierwszych dekad XXI wieku. Analizy wskazują, że samorządy obu badanych państw doświadczyły implementacji rozwiązań zaczerpniętych z różnych i pod wieloma względami sprzecznych paradygmatów zarządzania. We wprowadzaniu reform zarządzania w samorządzie terytorialnym obu państw występowały zarówno trendy zbieżne, jak i rozbieżne. Reformy na Węgrzech po 2010 roku odzwierciedlają spójną wizję silnego i scentralizowanego państwa mającego zapewnić skuteczne rozwiązywanie problemów społecznych. Rynkowi i społeczeństwu obywatelskiemu wyznaczono niewielką rolę. Odnośnie polskiego samorządu terytorialnego, obecnie trudno wskazać jeden organizacyjny model stanowiący spójną całość.
Reformy zarządzania w polskim i węgierskim samorządzie terytorialnym
Keywords: management models; Poland; Hungary; modele zarządzania; Polska; Węgry